Clonogenic Multiple Myeloma Progenitors, Stem Cell Properties, and Drug Resistance - Matsui, William (2008)
Many agents are active in multiple myeloma, but the majority of patients relapse. This clinical pattern suggests most cancer cells are eliminated, but cells with the clonogenic potential to mediate tumor regrowth are relatively chemoresistant. Our previous data suggested that CD138(+) multiple myeloma plasma cells cannot undergo long-term proliferation but rather arise from clonogenic CD138(neg) B cells. We compared the relative sensitivity of these distinct cell types to clinical antimyeloma agents and found that dexamethasone, lenadilomide, bortezomib, and 4-hydroxycyclophosphamide inhibited CD138(+) multiple myeloma plasma cells but had little effect on CD138(neg) precursors in vitro. We further characterized clonogenic multiple myeloma cells and stained cell lines using the Hoechst side population and Aldefluor assays. Each assay identified CD138(neg) cells suggesting that they possess high drug efflux capacity and intracellular drug detoxification activity. We also found that multiple myeloma cells expressing the memory B-cell markers CD20 and CD27 could give rise to clonogenic multiple myeloma growth in vitro and engraft immunodeficient nonobese diabetes/severe combined immunodeficient mice during both primary and secondary transplantation. Furthermore, both the side population and Aldefluor assays were capable of identifying circulating clonotypic memory B-cell populations within the peripheral blood of multiple myeloma patients. Our results suggest that circulating clonotypic B-cell populations represent multiple myeloma stem cells, and the relative drug resistance of these cells is mediated by processes that protect normal stem cells from toxic injury.